Influence Of Social Media Marketing, E-Commerce, and Product Innovation on Marketing Performance (Study on Food and Beverage SMEs in Surabaya) - Mia Adistia; Sanaji Sanaji (Journal of Business and Management Review, 2022)
This research aims to analyze the impact of social media marketing on marketing performance, the effect of E-Commerce on marketing performance, and the effect of product innovation on marketing performance. The sample used is MSME actors in Surabaya who sell food and beverages by utilizing social media and E-Commerce. Data were collected using a research questionnaire distributed to 155 respondents. The data analysis technique used multiple linear regression analysis performed by the SPSS-25 version program. The results show that social media marketing has a positive and significant impact on marketing performance, E-Commerce has a positive and significant effect on marketing performance, and product innovation has a positive and significant impact on marketing performance.